Construction of iron oxide nanoparticle-based hybrid platforms for tumor imaging and therapy. (29th January 2018) - Hu, Yong; Mignani, Serge; Majoral, Jean-Pierre; Shen, Mingwu; Shi, Xiangyang
Abstract : This review highlights the most recent progress in the construction of iron oxide nanoparticle-based hybrid platforms for tumor imaging and therapy. Abstract : The aim of this original review is to highlight and analyze the most recent progress and challenges in the synthesis and surface modifications of superparamagnetic iron oxide (Fe3 O4 ) nanoparticles (NPs) for multimodal imaging and therapy applications, which represent important fields in medicine in general and cancer in particular. Thus, the oncology domain is rapidly moving to a more personalized medicine including precision imaging and theranostic approaches. Novel biocompatible Fe3 O4 nanoparticulate systems have been designed for enhanced and targeted cellular uptake by surface layer coating modifications, to have improved r 2 relaxivity for sensitive magnetic resonance (MR) imaging applications, to have the ability to be used for dual mode imaging, and to be used for imaging-guided cancer therapy. In this review, we analyzed in depth the new strategies for generating biocompatible multifunctional Fe3 O4 nanoplatforms for both the diagnosis and therapy of cancer.